Is Employee Performance Affected by Organizational Cuoture, Work Motivation and Organizational Citizenship Behavior (OCB)?: An Empirical Investigation - Muzakki Muzakki; Anis Eliyana; Ridan Muhtadi (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2019)
The purpose of this research is to examine and analyze the influence of organizational culture, work motivation and organizational citizenship behavior (OCB) to employee performance. This research is conducted in Pamekasan Regency Government. The samples of this research are 116 respondents. The sample technique which used in this research is proportional stratified random sampling. This study employs questionnaire by a large number of answers based on a 5-point likert scale to collect the needed data and information. The result of this research reveals that the work motivation and organizational citizenship behavior (OCB) influence to employee performance significantly. Nevertheless, organizational culture has not significant effect on employee performance at Pamekasan Regency Government.